Introducing students to the application of statistics and investigative methods in political science. (10th March 2017) - Wells, Dominic D.; Nemire, Nathan A.
Summary: This exercise introduces students to the application of statistics and its investigative methods in political science. It helps students gain a better understanding and a greater appreciation of statistics through a real world application.